Development technique of xenon composite over-wrap pressure vessel for electric propulsion system. Issue 1 (1st August 2022) - Ma, Tianju; Yu, Bin; Zhao, Jipeng; Gu, Sendong; Yang, Wenbo; Ouyang, Ruijie; Gu, Shanshan
Abstract: The quality, reliability and safety of composite over-wrap pressure vessel (COPV) are strongly depended on manufacture process technology level in terms of discreteness of composite structure and winding process. In fact, the present qualification testing, acceptance testing and non-destructive evaluation techniques only can indirectly proof the quality of COPV, and do not presently adequately verify COPV reliability and safety characteristics. It is necessary to analyse various requirements of COPV manufacture process and corresponding influencing factors. There are 24 COPV development requirements which are specified in the ANSI/AIAA S-081A (S-081A) standard. According to the development requirements, the corresponding structure design, manufacture process and quality test solutions are formulated after comprehensive analysis and discussion. This paper introduced the manufacture process variables that affect the quality, reliability and safety of COPV. The COPV, which will be used to electric propulsion system of space system, were developed successfully by the optimized manufacture process technology. The impact-damage protection plan is illustrated in terms of the whole life cycle of COPV, including fabrication, test, transportation, storage and full stage.